Characterization and changes in polyphenol oxidase from eggplant fruit (Solanum melongena L.) during storage at low temperature - Concellón, Analía (2004)
Polyphenoloxidase (PPO) from eggplant fruit was characterized, and its catecholase activity studied during storage of fruit at 0 and 10ºC. The high catecholase activity was observed using 4-methylcatechol as substrate at pH 6 and 30ºC and activation with sodium dodecyl sulphate (SDS) was unnecessary. The soluble PPO fraction was the most thermostable, as well as the most active, form of the enzyme. Fruits stored at 10ºC were undamaged, whereas those kept at 0 and 5ºC experienced chilling injury from days 6 and 8, respectively, as indicated by the decrease of lightness (L0) of pulp tissue. During exposure of fruits at 10ºC, the activities of soluble and insoluble PPO fractions increased, whereas, at 0ºC, PPO activity of both fractions decreased and maintained lower levels when browning of pulp tissue was observed. Soluble PPO activity at 0ºC was directly related to the value for L0.